RANCANGAN SISTEM PENUNJANG KEPUTUSAN DALAM MENENTUKAN REKOMENDASI VAPORIZER BAGI PEMBELI PADA TOKO INDVAPORSHOP DENGAN METODE WEIGHTED PRODUCT - Julian, Dwitri Ono (Universitas Multi Data Palembang, 2024)
Vapor is an alternative substitute for tobacco cigarettes with many fans from different sectors so vapor becomes a widespread trend, Indvaporshop is a vapor shop that is a place of research that aims to explore buyers in determining vapor products that meet the purchaser's criteria, aspects on criteria determined based on specifications on each product such as brand, category, battery, watt, as well as the price on each vapor product, with 20 vapour product data and 5 specification criteria obtained on the basis of the owner's interview, the use of the Weighted Product motode as the calculation process used in this study. The overall recommended result on all steam pods is HexOhm v3 Anodized with a value of 0.0662. While recommendations based on criteria such as branded Vaporesso, category “MOD”, battery capacity 2200 mAh, 220 watt at a price below Rs. 800,000 will give the Vaporeso Luxe II results.